2016
DOI: 10.1021/acs.joc.6b00997
|View full text |Cite
|
Sign up to set email alerts
|

An Explicit Interpretation of the Directing Group Effect for the Pd(OAc)2-Catalyzed Aromatic C–H Activations

Abstract: A comprehensive DFT investigation has been performed for a series of the Pd(OAc)2-catalyzed C-H activations, updating and extending the understanding of directing group effect. In the beginning, the directed and undirected C-H activation mechanisms, based on 10 model reactions, have been discussed comparatively, which disclosed that directing group can exert a thermodynamic driving force, not necessarily a kinetic promotion, on the C-H activation process. Formation of the open palladation species via the undir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 102 publications
1
10
0
1
Order By: Relevance
“…A heteroaromatic substituent able to coordinate to the palladium atom is required for intermolecular DAA . The coordination leads to a cyclopalladated intermediate, and governs the regioselectivity of the alkoxylation . Thus, this review is organized according to the type of the coordinating substituent and, mostly, the chronological order of the reports.…”
Section: Introductionmentioning
confidence: 99%
“…A heteroaromatic substituent able to coordinate to the palladium atom is required for intermolecular DAA . The coordination leads to a cyclopalladated intermediate, and governs the regioselectivity of the alkoxylation . Thus, this review is organized according to the type of the coordinating substituent and, mostly, the chronological order of the reports.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, no Pd-catalyzed DHR of pyridine N-oxides was published since 2010 [73] 4 . The mechanism of the Pd(OAc) 2 -mediated C-H activation of pyridine N-oxide has however been investigated by Fang and Zhang through density functional theory (DFT) calculations [75]. While coordination of the catalyst to the N-oxide was previously proposed as the step directing the regioselectivity of the C-Pd bond formation [76], DFT calculations indicated that the undirected mechanism is more plausible than the 4-memberdirected one both thermodynamically and kinetically [75].…”
Section: Pyridine N-oxidesmentioning
confidence: 99%
“…Detailed analysis on the C2‐selectivity of quinoline N‐oxides has been deficient in the literature. For example, it was not very clear whether C2−H activation would be assisted by the directing group center, considering that the formation of four‐member palladacycles might be quite unusual; otherwise, it would proceed via the undirected mechanism involving open (i. e., acyclic) palladated species . In this study, we present a series of density functional theory (DFT) calculations to locate the plausible reaction mechanisms leading to the preferred C2−H activation.…”
Section: Introductionmentioning
confidence: 99%
“…The electron‐rich oxygen atom appears to be the directing group center of quinoline N‐oxides, in which C2−H activation would afford four‐member palladacycles as possible intermediates. Considering five‐member palladacycles should be more common than the four‐member counterparts, C8−H activation might be thought as a competitive reaction path. However, experimental results demonstrated that C2−H activation was strongly preferred and functionalizations on the other positions were incompetitive…”
Section: Introductionmentioning
confidence: 99%